1994
DOI: 10.1159/000247171
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of <i>Chlamydia trachomatis</i> with a Nucleic Acid Probe in Male and Female Patients

Abstract: To evaluate a commercially available DNA hybridization test, the Gen-Probe Pace 2 assay (GP) was compared with the Chlamydiazyme (CZ) for the detection of Chlamydia trachomatis in urethral and endocervical specimens. Samples were collected from 300 persons, including 199 registered and 43 nonregistered female prostitutes, examined for screening purposes, as well as 22 male and 36 female symptomatic sexually transmitted disease (STD) patients. The overall prevalence of C. trachomatis was 7.3% in all persons exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, factors such as specimen adequacy due to collection, transport time, and storage of the sample can negatively influence the sensitivity of cell culture (1,15). Thus, new methods for diagnosis were developed, such as direct immunofluorescence, enzyme immunoassays, and DNA probe techniques (2,12,13,18,(20)(21)(22), for use in clinical practice. However, despite the advantages of these assay systems, including ease of transport and lower cost than cell culture, the numbers of infectious organisms in clinical samples were frequently too few to be detected by either culture or antigen or DNA probe assays.…”
mentioning
confidence: 99%
“…However, factors such as specimen adequacy due to collection, transport time, and storage of the sample can negatively influence the sensitivity of cell culture (1,15). Thus, new methods for diagnosis were developed, such as direct immunofluorescence, enzyme immunoassays, and DNA probe techniques (2,12,13,18,(20)(21)(22), for use in clinical practice. However, despite the advantages of these assay systems, including ease of transport and lower cost than cell culture, the numbers of infectious organisms in clinical samples were frequently too few to be detected by either culture or antigen or DNA probe assays.…”
mentioning
confidence: 99%
“…Nucleic acid probe assays have been shown to be effective tools for screening for Chlamydia trachomatis (1,(4)(5)(6)(7)(8)(9). Numerous reports have demonstrated that this method is as sensitive as enzyme immunoassays (5)(6)(7)(8)(9) or culture (1,4). The use of the method has become widespread for testing of women in family planning settings and men and women seen at sexually transmitted disease clinics.…”
mentioning
confidence: 99%